Development of tool life prediction model of TIALN coated tools during the high speed hard milling of AISI H13 steel - Khalid, A. K. H.; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul; Lajis, Mohd Amri (2007)
This paper presents the result of an experimental investigation on tool wear during the high speed end milling of AISI H13 tool steel by TiAlN coated carbide insert under dry cutting condition. Sufficient numbers of experiment were run based on the central composite design (CCD) concept of response surface methodology (RSM) in order to generate tool life data. An empirical second order model in terms of cutting speed, feed and axial depth of cut has been developed for the effective prediction of tool life. The adequacy of the model has been verified by ANOVA under 95% confidence interval